2018
DOI: 10.1186/s12929-018-0435-3
|View full text |Cite
|
Sign up to set email alerts
|

Avicequinone B sensitizes anoikis in human lung cancer cells

Abstract: BackgroundDuring metastasis, cancer cells require anokis resistant mechanism to survive until reach the distant secondary tissues. As anoikis sensitization may benefit for cancer therapy, this study demonstrated the potential of avicequinone B, a natural furanonaphthoquinone found in mangrove tree (Avicenniaceae) to sensitize anoikis in human lung cancer cells.MethodsAnoikis inducing effect was investigated in human lung cancer H460, H292 and H23 cells that were cultured in ultra-low attachment plate with non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
3
18
2
Order By: Relevance
“…As can be seen in Figure 2A green fluorescence). This result differs from that obtained by Prateep et al 8 who reported the induction of apoptosis, but not necrosis, in H460 cells treated with avicequinone B. This discrepancy might be explained by the differences in the experimental setting, since they used a mild test concentration (lower than the IC 50 ).…”
Section: Anti-proliferative Effect Of Avicequinone B Occurs By Arrestcontrasting
confidence: 92%
See 4 more Smart Citations
“…As can be seen in Figure 2A green fluorescence). This result differs from that obtained by Prateep et al 8 who reported the induction of apoptosis, but not necrosis, in H460 cells treated with avicequinone B. This discrepancy might be explained by the differences in the experimental setting, since they used a mild test concentration (lower than the IC 50 ).…”
Section: Anti-proliferative Effect Of Avicequinone B Occurs By Arrestcontrasting
confidence: 92%
“…Notably, ERK activation/expression is involved in the cellular response to environment regulating cell cycle and cellular differentiation and senescence, which is critical for cancer initiation and progression ( Figure S4). In agreement, Patreep et al 8 demonstrated that the inhibition of ERK phosphorylation by avicequinone B is an important mechanism involved in the induction of detachment-induced cell death, also known as anoikis, in resistant lung cancer cells. Taken together, this experimental evidence demonstrates that ERK-related signaling pathways play an important role in the cytotoxic effect of the test compound against cancer cells.…”
Section: Transcriptome Sequencing Revealed That Avicequinone B Promotsupporting
confidence: 56%
See 3 more Smart Citations